Unsupervised Domain Adaptation Via Dynamic Clustering and Co-Segment Attentive Learning for Video-Based Person Re-Identification - Fuping Zhang; Fengjun Chen; Zhonggen Su; Jianming Wei (IEEE Access, 2024)
Currently, supervised person re-identification (Re-ID) models trained on labeled datasets can achieve high recognition performance in the same data domain. However, accuracy drops dramatically when these models are directly applied to other unlabeled datasets or natural environments, due to a significant sample distribution gap between the two domains. Unsupervised Domain Adaptation (UDA) methods can solve this problem by fine-tuning the model on the target dataset with pseudo-labels generated by the clustering method. Yet, these methods are primarily aimed at the image-based person Re-ID domain. This is because the background noise and interference information are complex and changeable in the video scenarios, resulting in large intra-class distances and small inter-class spaces, which easily lead to noisy labels. Huge domain gap and noisy labels hinder clustering and training processes heavily in the video-based person Re-ID. To address the problem, we propose a novel UDA method via Dynamic Clustering and Co-segment Attentive Learning (DCCAL) for it. DCCAL includes a Dynamic Clustering (DC) module and a Co-segment Attentive Learning (CAL) module. The DC module is responsible for adaptively clustering pedestrians within different generation processes to alleviate noisy labels. On the other hand, the CAL module reduces the domain gap using a co-segmentation-based attention mechanism. Additionally, we introduce Kullback-Leibler (KL) divergence loss to reduce the distribution of features between two domains for better performance. Experimental results on two large-scale video-based person Re-ID datasets, MARS and DukeMTMC-VideoReID (DukeV), demonstrate exceptional precision performance. Our method outperforms state-of-the-art semi-supervised and unsupervised approaches by 1.1% in Rank-1 and 1.5% in mAP on DukeV, as well as 3.1% and 2.1% in Rank-1 and mAP on MARS, respectively.